Depressão e suicídio: estudos de casos de alunos do curso de letras da universidade federal do Tocantins/Araguaína. - Freitas, Lidiane Alves de (Universidade Federal do Tocantins, 2022)
Suicide is today one of the leading causes of death among young people and has as one of the facilitating factors depression, so this paper aims to understand the perception of illness by depression in four students of the Letters course at the Federal University of Tocantins. To this end, a literature review is made elucidating the concepts of depression and suicide from the pathological point of view, emphasizing incidence, diagnosis and treatment, as well as a survey of studies on the illness of college students, demonstrating an incidence larger than the general population, which justifies the importance of this work. To conduct the research we used a case study through data collection by semi-directed interviews with four students who reported having attempted suicide, so the sample was intentional. The interviews were recorded and transcribed. The analysis was made through content analysis and resulted in the interviewees' perception of what caused their emotional study in the past, as it currently stands, the perception of their suicidal thoughts and the University's role. Several factors are considered to have contributed to depression, including financial, family, loneliness, burden, lack of access to treatment, and the university functioned as an aid to emotional support.